Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10661-015-4581-8
|View full text |Cite
|
Sign up to set email alerts
|

Visibility characteristics and the impacts of air pollutants and meteorological conditions over Shanghai, China

Abstract: In China, visibility condition has become an important issue that concerns both society and the scientific community. In order to study visibility characteristics and its influencing factors, visibility data, air pollutants, and meteorological data during the year 2013 were obtained over Shanghai. The temporal variation of atmospheric visibility was analyzed. The mean value of daily visibility of Shanghai was 19.1 km. Visibility exhibited an obvious seasonal cycle. The maximum and minimum visibility occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The changes in its concentration mainly resulted from the changes in the weather conditions (insolation intensity, air temperature) and the participation of the O3 precursors (e.g., nitrogen oxides, hydrocarbons and other pollutants participation in the O3 formation) in the atmospheric air [30,39]. Since the visibility is strongly affected by air pollutants [1,40,41], the presence of its' weaker variation over Warsaw from 2004-2013 is found. In Poland, considerable changes in air pollution were observed from 1980-2000 [42].…”
Section: General Description Of Visibility Meteorology and Air Pollumentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in its concentration mainly resulted from the changes in the weather conditions (insolation intensity, air temperature) and the participation of the O3 precursors (e.g., nitrogen oxides, hydrocarbons and other pollutants participation in the O3 formation) in the atmospheric air [30,39]. Since the visibility is strongly affected by air pollutants [1,40,41], the presence of its' weaker variation over Warsaw from 2004-2013 is found. In Poland, considerable changes in air pollution were observed from 1980-2000 [42].…”
Section: General Description Of Visibility Meteorology and Air Pollumentioning
confidence: 99%
“…PC1, PC2, PC3 and PC4 can be interpreted as major factors that control visibility [1,6,17,40]. Visibility (Vis), O3 concentration (O3), NO2 concentration (NO2), CO concentration (CO), air temperature (T), relative air humidity (RH), PM10 concentration (PM10) and insolation intensity (Rad) were most strongly correlated with PC1.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…To understand the characteristics and factors affecting AV, studies have been carried out in highly developed regions all over the world [3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22]. Wang et al (2009) revealed that since the mid-1980s, AV has increased in Europe and North America, but has decreased substantially over south and east Asia, South America, Australia, and Africa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sabetghadam et al (2012) analyzed AV data collected during 1958-2008 from the historical airport AV database in Tehran, Iran, and found decreasing trends in AV from all of the database's monitoring stations [17]. In recent years, studies that have occurred in China (e.g., Shanghai [18,19], Beijing [20][21][22], and Guangzhou [22]) have shown increasing trends of AV. Overall, previous studies have revealed that developed countries display a general increasing trend of AV after the mid-1980s, whereas developing countries display substantially decreasing trends of AV due to rapid economic development-this is especially true in China [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, their study suggested that visibility and microphysical parameters are nonlinearly related to each other and RH and Nd, LWC are most important parameters for fog visibility calculation [5,22]. Xue et al [24] studied the effects of air pollution and meteorological elements on visibility in Shanghai, China; their results showed that air temperature and wind speed are positively correlated with visibility, while relative humidity is negatively correlated with visibility. Hong [25] studied the relationship between visibility and its influencing factors based on binary correlation and partial correlation methods.…”
Section: Influencing Factors On Visibilitymentioning
confidence: 99%